2013
DOI: 10.1002/mds.25280
|View full text |Cite
|
Sign up to set email alerts
|

Latah: An indonesian startle syndrome

Abstract: The nature of culture-specific startles syndromes such as "Latah" in Indonesia and Malaysia is ill understood. Hypotheses concerning their origin include sociocultural behavior, psychiatric disorders, and neurological syndromes. The various disorders show striking similarities despite occurring in diverse cultural settings and genetically distant populations. They are characterized clinically by exaggerated startle responses and involuntary vocalizations, echolalia, and echopraxia. Quantifying startle reflexes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 31 publications
(56 reference statements)
0
14
0
Order By: Relevance
“…Other reported etiologies are early‐onset schizophrenia and membranous lipodystrophy . Finally, palilalic behaviors may also be encountered in functional neurological disorders and in culture‐bound startle syndromes (eg, Indonesian Latah; also see below) . Of note, palilalia should be distinguished from stuttering, a disorder with dysfluency of speech and repetition of sounds, syllables, or words (eg, Video 1A, palilalia vs Video 1K, stuttering) …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other reported etiologies are early‐onset schizophrenia and membranous lipodystrophy . Finally, palilalic behaviors may also be encountered in functional neurological disorders and in culture‐bound startle syndromes (eg, Indonesian Latah; also see below) . Of note, palilalia should be distinguished from stuttering, a disorder with dysfluency of speech and repetition of sounds, syllables, or words (eg, Video 1A, palilalia vs Video 1K, stuttering) …”
Section: Methodsmentioning
confidence: 99%
“…96 Finally, palilalic behaviors may also be encountered in functional neurological disorders 52 and in culture-bound startle syndromes (eg, Indonesian Latah; also see below). 97 Of note, palilalia should be distinguished from stuttering, a disorder with dysfluency of speech and repetition of sounds, syllables, or words (eg, Video 1A, palilalia vs Video 1K, stuttering). 98,99 Echolalia Echolalia is the automatic imitative repetition of sounds, words, or phrases in the absence of explicit awareness.…”
Section: Palilaliamentioning
confidence: 99%
See 1 more Smart Citation
“…), many of which are stereotypical and similar across cultures. Bakker et al (2013) compared eyeblink EMG measures of startle in Latah patients with those of matched control participants and found that this measure of startle was larger and more probable in the patients, but no differences in onset latency or habituation were found. However, startle components in the neck and body muscles were more probable and faster in patients, and they habituated more slowly.…”
Section: Culture-specific Startle Disordersmentioning
confidence: 96%
“…Additionally, an example of a normal startle response with a secondary abnormal response is startle epilepsy, a condition in which a normal startle results in a focal frontal lobe seizure (10,12). Examples of exaggerated startle responses that may represent pathological syndromes in specific ethnic groups (10,12) including Latah in Malay people (13)(14)(15), Jumping Frenchmen of Maine (16), and Ragin' Cajuns of Louisiana (17). For example, Latah can be triggered by sudden shock resulting in screaming, dancing and cursing.…”
Section: Introductionmentioning
confidence: 99%